2020
DOI: 10.3390/foods9101503
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Enzymatic Protein Hydrolysis of By-Products from Seabream (Sparus aurata) and Seabass (Dicentrarchus labrax), Chemical and Functional Characterization

Abstract: Valorization of seabass and seabream by-products is becoming increasingly relevant, as marketing of these species moves from selling whole fish to filleting for convenience products. With this aim, we optimized for the first time the production of fish protein hydrolysates (FPH) by enzymatic hydrolysis from filleting by-products of these commercially relevant aquaculture species, isolating fish oil at the same time. On the whole, both fish yielded similar amounts of protein, but frames and trimmings (FT) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…The percentage of protein in sea bass side streams (dry weight, dw) was 79.18 ± 0.36, 48.08 ± 0.55, 18.24 ± 1.07, 52.14 ± 5.32, and 49.87 ± 0.89 for muscle, heads, viscera, skin, and tailfins, respectively. These results are in close agreement with the values recently reported by Munekata et al [ 8 ] and Valcarcel et al [ 7 ] (except for tailfins that have not been considered in those studies). Regarding protein recovery from fish side streams samples, the percentage was calculated by applying the following equation: (amount of protein in extract/amount of protein in lyophilized sample) × 100.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The percentage of protein in sea bass side streams (dry weight, dw) was 79.18 ± 0.36, 48.08 ± 0.55, 18.24 ± 1.07, 52.14 ± 5.32, and 49.87 ± 0.89 for muscle, heads, viscera, skin, and tailfins, respectively. These results are in close agreement with the values recently reported by Munekata et al [ 8 ] and Valcarcel et al [ 7 ] (except for tailfins that have not been considered in those studies). Regarding protein recovery from fish side streams samples, the percentage was calculated by applying the following equation: (amount of protein in extract/amount of protein in lyophilized sample) × 100.…”
Section: Resultssupporting
confidence: 93%
“…Preventive measures adopted by the EU to reduce the catch of wild sea bass has resulted in an increase in cultured sea bass [ 6 ]. In 2017, the production of sea bass from aquaculture accounted for 15% of the total farmed fish worldwide [ 7 ]. On the other hand, the growing development of both convenience food items and active packaging has led to a change in the commercialization of fishery products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of value, one of the most significant growths in recent years was obtained for European gilthead sea bream ( Sparus aurata ), reaching 94.936 tons and 485 million EUR in 2017 [ 2 ]. This trend is supported by the increased demand, which, together with the consumer growing interest in convenience products, has led to a greater manufacture of gutted and filleted sea bream [ 3 ]. In this sense, Pateiro et al [ 4 ] reported that discards accounted for ~60% of the whole sea bream after the filleting process.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they suggested sea bream side stream materials as a promising source of valuable compounds to be exploited for human consumption. In this way, fish protein hydrolysates with a remarkable essential amino-acid profile were produced from sea bream filleting side streams and were considered as a suitable tool for developing food additives and supplements [ 3 ]. Currently, only industrially processed feeds are used to grow gilthead sea bream in aquaculture systems [ 7 ].…”
Section: Introductionmentioning
confidence: 99%